Freeze-thaw resistant fabricated pavement prefabricated slab material and preparation method thereof
By using LC3 cement, PE fiber, HPP fiber, polybutadiene rubber and polycarbonate in prefabricated board materials for prefabricated pavement, the problem of insufficient freezing resistance in seasonal areas is solved, and the material's freezing resistance and durability are significantly improved.
Patent Information
- Application Number
- CN202411802391.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-07
AI Technical Summary
The long-term freezing of prefabricated pavements in seasonal areas leads to structural damage, affecting the performance of use, and the existing concrete materials have insufficient freezing resistance.
Limestone calcined clay cement (LC3 cement) is used to combine polyethylene fiber (PE fiber) and polypropylene plastic steel fiber (HPP fiber), and polybutadiene rubber and polycarbonate are added, and polycarboxylic acid high-efficiency water reducer and polyacrylamide antifreeze. Through the combination of these materials and additives, the antifreeze properties of concrete are significantly improved.
It significantly improves the freezing resistance and durability of concrete, reduces damage to the pavement structure caused by freeze-thaw cycle, and is suitable for prefabricated pavement prefabricated panels in seasonal areas.
Smart Images

Figure BDA0005178348380000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete materials, and in particular to a freeze-thaw resistant assembled pavement prefabricated board material and a preparation method thereof. Background Art
[0002] Prefabricated pavement technology refers to a type of technology that completes the prefabrication of the pavement structure layer in the factory, transports it to the construction site for assembly, joint treatment and other subsequent processes to complete the rapid construction of the pavement structure. Compared with traditional concrete pavement, the future development of prefabricated pavement tends to be mechanized and automated, using a complete set of mechanized equipment, from the prefabrication of the pavement system in the factory to the assembly operations corresponding to different application occasions.
[0003] The use of prefabricated pavement must take into account its load-bearing capacity and durability. For seasonal areas, such as areas with long winters and low temperatures, the pavement will be frozen for a long time, which will cause damage to the internal structure of the pavement and affect the performance of the pavement.
[0004] The frost resistance of concrete refers to the ability of concrete materials to resist multiple freeze-thaw cycles when they are saturated with water. Porosity is the main factor affecting the frost resistance of materials. The volume of water in the pores will expand when it freezes, which will exert pressure on the pores and cause cracks in the pore walls. After multiple freeze-thaw cycles, the material will be severely damaged.
[0005] In order to meet the long-term use of prefabricated pavements in seasonal areas, anti-freeze performance is also particularly critical while meeting the bearing capacity. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a freeze-thaw resistant assembled pavement prefabricated board material and a preparation method thereof.
[0007] The present invention provides a freeze-thaw resistant assembled pavement prefabricated board material, comprising the following raw materials in parts by weight: 750-870 parts of cementitious material, 280-320 parts of fine aggregate, 1-5 parts of water reducer, 1-3 parts of antifreeze agent, 2-5 parts of polyethylene fiber (PE fiber), 2-5 parts of polypropylene plastic steel fiber (HPP fiber), 20-30 parts of polybutadiene rubber, 30-45 parts of polycarbonate, and 120-170 parts of water;
[0008] The cementitious material includes 210-270 parts of cement, 60-80 parts of silica fume, and 480-520 parts of fly ash;
[0009] The cement is limestone calcined clay cement (LC3 cement), which includes the following raw materials in weight percentage: 100-150 parts of cement clinker, 30-50 parts of limestone, 10-15 parts of gypsum and 70-90 parts of kaolin calcined clay.
[0010] The LC3 cement used in the present invention refers to limestone and calcined clay replacing cement clinker in a certain proportion, and gypsum is added at the same time, which is a green low-carbon silicate cement. At the same time, the raw material kaolin of calcined clay is abundant in resources, and low-temperature calcination does not produce carbon dioxide. It replaces part of the silicate cement clinker, which not only reduces the carbon emission in the cement production process, but also maintains good mechanical properties. Calcination converts kaolinite in clay powder into metakaolin, which has volcanic ash activity, so that when calcined clay is used in LC3 cement, the strength of LC3 cement is improved, and the volcanic ash reaction makes LC3 cement have a small porosity, a dense structure and good durability. Compared with ordinary silicate cement, LC3 cement has better antifreeze performance. Kaolin calcined clay contains more aluminum oxide, which can react with cement hydration product calcium hydroxide to generate AFt (calcium vanadate) to promote strength growth; at the same time, aluminum oxide can react with limestone to generate AFm (monosulfur type hydrated calcium sulfoaluminate) phase to inhibit the decomposition of calcium vanadate and maintain stable strength. The pozzolanic reaction makes LC3 cement have small porosity, dense structure and good durability.
[0011] As a preferred technical solution of the present invention, the fine aggregate is quartz sand with a particle size of 160 to 200 μm; the water reducer is a polycarboxylic acid high-efficiency water reducer with a water reduction rate greater than 20%; the antifreeze agent is a polyacrylamide antifreeze agent; the fly ash is low-calcium fly ash with a calcium content of less than 10wt%; the silica ash is highly active microsilica ash with a particle size of 0.1 to 0.15 μm and a silicon dioxide content greater than 90wt%; and the water is ordinary tap water.
[0012] Polycarboxylic acid high-efficiency water reducing agent and polyacrylamide antifreeze agent are used. The water reducing agent can significantly reduce the water-cement ratio of concrete and reduce the amount of water used, thereby improving the strength and density of concrete, and further improving the antifreeze durability of concrete materials. Antifreeze agents can inhibit the formation of ice crystals in concrete, thereby reducing the damage caused by ice crystals to concrete. At the same time, antifreeze agents can form a protective film in concrete, improve the density of concrete, effectively reduce the porosity and capillary pore size in concrete, improve the structure of concrete, and improve antifreeze performance.
[0013] As a preferred technical solution of the present invention, the diameter of the polyethylene fiber is 20-40 μm, the length is 6-18 mm, and the density is 0.95-0.98 g / cm 3 The tensile strength can reach 3000MPa; the diameter of the polypropylene plastic steel fiber is 700-900μm, the length is 24-32mm, and the density is 0.9-0.98g / cm 3 , the tensile strength is about 800MPa.
[0014] The main role of PE fiber and HPP fiber in concrete is to bond with the cement matrix, thereby improving the strength and ductility of concrete. When fiber concrete is subjected to freeze-thaw cycles, the free water inside the concrete freezes, and the volume expands to produce stress. The addition of fibers can produce more pores and channels, thereby relieving and dispersing certain concentrated stresses, slowing down the destruction of concrete and improving its freeze-thaw cycle resistance.
[0015] As a preferred technical solution of the present invention, the density of the polybutadiene rubber is 0.88-0.92 g / cm 3 The particle size is 0.05-3.5 μm, the cold resistance is particularly excellent (Tg = 100 ° C), and the density of polycarbonate is 1.18-1.22 g / cm 3 .
[0016] Polybutadiene rubber has excellent elasticity and crack resistance, which can significantly improve the freeze-thaw resistance of concrete, provide excellent waterproof performance, and reduce water penetration. Polycarbonate has excellent impact resistance and durability, which can significantly improve the freeze-thaw resistance of concrete. The unsaturated bonds in polybutadiene rubber will undergo cross-linking reactions with cement-based materials, preventing the development of concrete cracks, thereby improving the strength and durability of the composite material. Polycarbonate, as an interface reinforcement material, enhances the bonding force between the cement matrix and aggregates, and polycarbonate undergoes certain chemical reactions with substances such as calcium hydroxide generated by hydration reactions to generate a macromolecular network interwoven structure bonded by ionic bonds, forming a more stable compound, making the concrete material more compact and enhancing the material's freeze-thaw resistance.
[0017] The present invention also provides a method for preparing the freeze-thaw resistant assembled pavement prefabricated board material according to the above-mentioned method, comprising the following steps:
[0018] (1) weighing the raw materials according to weight, mixing cement clinker, limestone, gypsum and kaolin calcined clay to obtain limestone calcined clay cement; mixing polyethylene fiber and polypropylene plastic steel fiber to obtain mixed fiber;
[0019] (2) mixing and stirring the limestone calcined clay cement, fine aggregate, fly ash, silica fume, antifreeze agent, and 1 / 2 to 2 / 3 of the weight of mixed fiber to obtain a cement-based material;
[0020] (3) Mix water and a water reducing agent, add the mixture to the cement-based material, continue stirring, then add the remaining 1 / 3 weight of the mixed fiber, stir again, and obtain the freeze-thaw resistant prefabricated pavement board material.
[0021] As a preferred technical solution of the present invention, the stirring rate in step (2) is 100-150 rpm and the time is 5 min; the continued stirring time in step (3) is 6 min and the re-stirring time is 5 min, and the stirring speed is 200-300 rpm.
[0022] As a preferred technical solution of the present invention, it also includes the steps of pouring the prepared concrete into a mold, removing the mold and curing to obtain a freeze-thaw resistant assembled pavement prefabricated slab.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The invention provides a freeze-thaw resistant assembled pavement prefabricated board material, which adopts limestone calcined clay cement, has a smaller porosity, is beneficial to improving the frost resistance of concrete, and has good mechanical properties and durability.
[0025] The fibers used are PE fibers and HPP fibers. Adding different types of fibers can improve the frost resistance of concrete. The fibers form a random structure in the concrete, enhance the internal restraint, reduce deformation during freeze-thaw cycles, and thus improve strength and frost resistance. The bridging effect of fiber composite mixing can weaken the expansion stress generated when water freezes, reduce damage to the matrix, and improve the frost resistance of concrete. At the same time, the bridging effect of the fibers constrains the floating of rubber particles to a certain extent, reduces the number of pores in the concrete structure, ensures the density of the concrete material, and improves the frost resistance.
[0026] The combined effect of water reducer and antifreeze agent can effectively improve the structure of concrete, reduce the porosity of concrete, improve the compaction performance, and thus improve the frost resistance.
[0027] Adding polybutadiene rubber and polycarbonate to cement can improve the toughness of the material and relieve the pressure caused by frost heave. At the same time, through physical modification and chemical reaction with cement, they can fill the pores of concrete, improve the density of concrete, reduce water permeability, and provide space for releasing the frost heave pressure of concrete, ultimately enhancing the freeze-thaw resistance of cement materials.
[0028] The concrete formed by the LC3 cement, PE fiber, HPP fiber, polybutadiene rubber, polycarbonate and antifreeze agent of the present invention has good antifreeze performance and is suitable for assembled pavement prefabricated panels in seasonal areas. DETAILED DESCRIPTION
[0029] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0030] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0034] In the following embodiments and comparative examples, the cement clinker used is PO 42.5 cement purchased from Conch Co., Ltd.; the particle size of the limestone used is 5-15nm; the composition of the gypsum is calcium sulfate dihydrate; kaolin calcined clay is purchased from Lingshou County, Hebei Province, and the calcination temperature is 600-900°C; the water reducer is a polycarboxylic acid high-efficiency water reducer with a water reduction rate of 20-40%; the antifreeze agent is a polyacrylamide antifreeze agent purchased from Jiangsu Zhonghao Yuanda; the fly ash is low-calcium fly ash with a calcium content of 5-10wt%, purchased from Jining, Shandong; the silica fume is a highly active micro-silica fume purchased from Jining, Shandong; the fine aggregate used is quartz sand with a particle size of 160-200μm and an average particle size of 170-180μm; the diameter of the PE fiber is 20-40μm, the length is 6-18mm, and the density is 0.95-0.98 / cm 3The diameter of HPP fiber is 700-900 μm, the length is 24-32 mm, and the density is 0.9-0.98 gg / cm 3 ; The density of polybutadiene rubber is 0.88~0.92g / cm 3 , particle size is 0.05~3.5μm, density of polycarbonate is 1.2g / cm 3 .
[0035] Example 1
[0036] The preparation steps of freeze-thaw resistant prefabricated pavement slab materials are as follows:
[0037] (1) The following raw materials were weighed in parts by weight: 125 parts of cement clinker, 38 parts of limestone, 12 parts of gypsum and 75 parts of kaolin calcined clay, and mixed and stirred to prepare LC3 cement.
[0038] (2) Weigh 250 parts of LC3 cement prepared in step (1), 300 parts of fine aggregate quartz sand, 490 parts of fly ash, 60 parts of silica fume, 5 parts of water reducer, 1 part of antifreeze agent, 2 parts of PE fiber, 2 parts of HPP fiber and 120 parts of water by weight. Mix the PE fiber and the HPP fiber to obtain mixed fiber.
[0039] (3) LC3 cement, quartz sand, fly ash, silica fume, antifreeze agent, and 2 / 3 weight of mixed fiber were stirred at low speed (150 rpm) for 5 minutes to fully mix the materials and obtain cement-based material.
[0040] (4) Take ordinary tap water and water reducer, fully blend, add to the cement-based material just stirred, and continue stirring for 6 minutes at a stirring speed of 250rpm. The cement undergoes hydration reaction, the fly ash and silica fume undergo pozzolanic reaction, the fine aggregate fills the gaps, the water reducer can reduce the amount of water, reduce the water-cement ratio, and improve the compactness of the concrete. The antifreeze agent can inhibit the formation of ice crystals, improve the structure of the concrete, and improve the antifreeze property. Add the remaining 1 / 3 of the mixed fiber and continue stirring for 5 minutes at a stirring speed of 250rpm to fully stir the materials and obtain concrete.
[0041] (5) Pour the prepared concrete into the mold, remove the mold after 24 hours, and then place it in a steam curing box for 48 hours. Take out the specimen for testing.
[0042] Example 2
[0043] The same as Example 1, except that the preparation method of LC3 cement in step (1) is different. In this embodiment, step (1) is: weigh the following raw materials by weight: 100 parts of cement clinker, 50 parts of limestone, 10 parts of gypsum and 90 parts of kaolin calcined clay, mix and stir evenly to prepare LC3 cement.
[0044] Example 3
[0045] The preparation steps of freeze-thaw resistant prefabricated pavement slab materials are as follows:
[0046] (1) The following raw materials were weighed in parts by weight: 125 parts of cement clinker, 38 parts of limestone, 12 parts of gypsum and 75 parts of kaolin calcined clay, and mixed and stirred to prepare LC3 cement.
[0047] (2) Weigh 250 parts of LC3 cement prepared in step (1), 300 parts of fine aggregate quartz sand, 490 parts of fly ash, 60 parts of silica fume, 5 parts of water reducer, 1 part of antifreeze agent, 2 parts of PE fiber, 2 parts of HPP fiber, 30 parts of polybutadiene rubber, 15 parts of polycarbonate and 120 parts of water by weight. Mix the PE fiber and the HPP fiber to obtain mixed fiber.
[0048] (3) LC3 cement, quartz sand, fly ash, silica fume, antifreeze agent, 2 / 3 weight of mixed fiber, polybutadiene rubber, and polycarbonate were stirred at a low speed (150 rpm) for 5 minutes to fully mix the materials and obtain a cement-based material.
[0049] (4) Take ordinary tap water and water reducing agent, fully blend them, add them to the cement-based material just stirred, and continue stirring for 6 minutes at a stirring speed of 250 rpm. Add the remaining 1 / 3 of the mixed fiber, continue stirring for 5 minutes at a stirring speed of 250 rpm to obtain concrete.
[0050] (5) Pour the prepared concrete into the mold and remove the mold for no less than 24 hours. Then place it in a steam curing box and cure it to the specified age. Take out the specimen and conduct the test.
[0051] Example 4
[0052] Same as Example 3, except that in step (2), the amount of polycarbonate is changed from 15 parts to 30 parts, and the rest is the same as Example 3.
[0053] Example 5
[0054] Same as Example 3, except that in step (2), the amount of polycarbonate is changed from 15 parts to 45 parts, and the rest is the same as Example 3.
[0055] Comparative Example 1
[0056] The preparation steps of freeze-thaw resistant prefabricated pavement slab materials are as follows:
[0057] (1) The following raw materials were weighed in parts by weight: 250 parts of PO 42.5 cement, 300 parts of fine aggregate quartz sand, 490 parts of fly ash, 60 parts of silica fume, 5 parts of water reducer, 1 part of antifreeze agent, 2 parts of PE fiber, 2 parts of HPP fiber and 120 parts of water. The PE fiber and the HPP fiber were mixed to obtain mixed fiber.
[0058] (2) Cement, quartz sand, fly ash, silica fume, antifreeze agent, and 2 / 3 weight of mixed fiber were stirred at a low speed (150 rpm) for 5 minutes to fully mix the materials and obtain a cement-based material.
[0059] (3) Take ordinary tap water and water reducing agent, fully blend them, add them to the cement-based material just stirred, and continue stirring for 6 minutes at a stirring speed of 250 rpm. Add the remaining 1 / 3 of the mixed fiber, continue stirring for 5 minutes at a stirring speed of 250 rpm to obtain concrete.
[0060] (5) Pour the prepared concrete into the mold, remove the mold after 24 hours, and then place it in a steam curing box for 48 hours. Take out the specimen for testing.
[0061] Comparative Example 2
[0062] The same as Example 4, except that no polybutadiene rubber is added during the preparation process, that is, polybutadiene rubber is deleted in both step (2) and step (3).
[0063] Comparative Example 3
[0064] The same as Example 4, except that polycarbonate is not added during the preparation process, that is, polycarbonate is deleted in both step (2) and step (3).
[0065] Comparative Example 4
[0066] The same as Example 4, except that the fiber is added at one time during the preparation process, that is, step (3) and step (4) are different from Example 4. Step (3): LC3 cement, quartz sand, fly ash, silica fume, antifreeze agent, mixed fiber, polybutadiene rubber, and polycarbonate are stirred at a low speed (150 rpm) for 5 minutes to fully mix the materials to obtain a cement-based material.
[0067] (4) Take ordinary tap water and a water reducing agent, fully blend them, add them to the cement-based material that has just been stirred, and continue stirring for 11 minutes at a stirring speed of 250 rpm to obtain concrete.
[0068] Effect verification
[0069] The performance of the test specimens prepared in Examples 1 to 5 and Comparative Examples 1 to 4 was tested. The detection basis of compressive strength, ultimate tensile strain, ultimate tensile strength, and compressive strength loss rate after 250 freeze-thaw cycles were respectively: "Concrete Strength Test and Evaluation Standard" GB / T 50081-2002 and "Concrete Freeze-Thaw Test Method" GB / T 50082-2009. The test results are shown in Table 1.
[0070] Table 1 Performance test results of each group of specimens
[0071]
[0072] As can be seen from the above table, the compressive strength loss of comparative example 1 is obvious after 250 freeze-thaw cycles, and the loss rate is as high as 48%. Examples 1 to 2 are LC3 cement, and the loss rate has been significantly reduced relative to ordinary cement. This is because the calcium carbonate in LC3 cement reacts with clay to generate zeolite and other products, which fill the pores of concrete, increase the density of concrete, thereby reducing the intrusion of water and improving the antifreeze performance. Examples 3 to 5 add polybutadiene rubber and polycarbonate, and the antifreeze performance is further improved. Polybutadiene rubber, as an elastomer, has excellent flexibility and can absorb and disperse stress caused by temperature changes (such as freeze-thaw cycles), and the unsaturated bonds in polybutadiene rubber will cross-link with cement-based materials, preventing the development of concrete cracks, thereby improving the strength and durability of the composite material. Polycarbonate, as an interface reinforcement material, enhances the bonding force between the cement matrix and the aggregate, and polycarbonate undergoes a certain chemical reaction with calcium hydroxide and other substances generated by hydration reaction to generate a macromolecular network interwoven structure bound by ionic bonds, forming a more stable compound, making the concrete material more compact and enhancing the material's anti-freeze-thaw performance. The anti-freeze performance changes with the change of the polycarbonate ratio, and the best anti-freeze performance is achieved when the polycarbonate: polybutadiene rubber ratio is 1.0.
[0073] By comparing Example 1 with Example 2, it can be found that as the kaolin calcined clay content increases, the compressive strength, tensile strength and tensile strain of the concrete increase, and the mass loss rate after freeze-thaw cycles decreases.
[0074] By comparing Example 2 with Example 4, it can be found that after removing the polybutadiene rubber component, the tensile strength and tensile strain decrease, and the mass loss rate after freeze-thaw cycles increases.
[0075] By comparing Example 3 with Example 4, it can be found that after removing the polycarbonate component, the tensile strength and tensile strain decrease, and the mass loss rate after freeze-thaw cycles increases.
[0076] By comparing Example 4 with Example 4, it can be found that after the fibers are added at one time, the tensile strength and tensile strain of the concrete decrease, and the mass loss rate after freeze-thaw cycles increases. This is because after all the fibers are added, they are entangled with each other and cannot be well dispersed, which affects the tensile properties and has a negative effect on the quality stability during the freeze-thaw cycle.
[0077] The above description is only a preferred specific implementation manner of the present invention, and the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, and they should be covered by the protection scope of the present invention.
Claims
1. A freeze-thaw resistant assembled pavement prefabricated board material, characterized in that: The invention comprises the following raw materials in parts by weight: 750-870 parts of cementitious material, 280-320 parts of fine aggregate, 1-5 parts of water reducing agent, 1-3 parts of antifreeze agent, 2-5 parts of polyethylene fiber, 2-5 parts of polypropylene plastic steel fiber, 20-30 parts of polybutadiene rubber, 30-45 parts of polycarbonate, and 120-170 parts of water; The cementitious material includes 210-270 parts of cement, 60-80 parts of silica fume, and 480-520 parts of fly ash; The cement is limestone calcined clay cement, which comprises the following raw materials in weight percentage: 100-150 parts of cement clinker, 30-50 parts of limestone, 10-15 parts of gypsum and 70-90 parts of kaolin calcined clay.
2. The freeze-thaw resistant assembled pavement prefabricated board material according to claim 1, characterized in that: The fine aggregate is quartz sand with a particle size of 160 to 200 μm; the water reducer is a polycarboxylic acid high-efficiency water reducer with a water reduction rate greater than 20%; the antifreeze agent is a polyacrylamide antifreeze agent; the fly ash is low-calcium fly ash with a calcium content of less than 10wt%; the silica ash is highly active microsilica ash with a particle size of 0.1 to 0.15 μm and a silicon dioxide content greater than 90wt%.
3. The freeze-thaw resistant assembled pavement prefabricated board material according to claim 1, characterized in that: The polyethylene fiber has a diameter of 20 to 40 μm, a length of 6 to 18 mm, and a density of 0.95 to 0.98 g / cm 3 The diameter of the polypropylene plastic steel fiber is 700-900 μm, the length is 24-32 mm, and the density is 0.9-0.98 g / cm 3 .
4. The freeze-thaw resistant assembled pavement prefabricated board material according to claim 1, characterized in that: The density of the polybutadiene rubber is 0.88-0.92 g / cm 3 , particle size is 0.05~3.5μm, density of polycarbonate is 1.18~1.22g / cm 3 .
5. A method for preparing a freeze-thaw resistant assembled pavement prefabricated board material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) weighing the raw materials according to weight, mixing cement clinker, limestone, gypsum and kaolin calcined clay to obtain limestone calcined clay cement; mixing polyethylene fiber and polypropylene plastic steel fiber to obtain mixed fiber; (2) mixing and stirring the limestone calcined clay cement, fine aggregate, fly ash, silica fume, antifreeze agent, and 1 / 2 to 2 / 3 of the weight of mixed fiber to obtain a cement-based material; (3) Mixing water and a water reducing agent, adding the mixture to the cement-based material, continuing to stir, then adding the remaining weight of the mixed fiber, stirring again, and obtaining the freeze-thaw resistant prefabricated pavement board material.
6. The preparation method according to claim 5, characterized in that: The stirring rate in step (2) is 100-150 rpm, and the time is 5 min; the time for continued stirring in step (3) is 6 min, and the time for further stirring is 5 min, and the stirring speed is 200-300 rpm.
7. The preparation method according to claim 5, characterized in that: The method also includes the steps of pouring the prepared concrete into a mold, removing the mold and maintaining the mold to obtain a freeze-thaw resistant assembled pavement precast panel.